Macroeconomic Models for Adjustment in Developing Countries. (International Monetary Fund, 1991)
This volume, edited by Mohsin S. Khan, Peter J. Montiel, and Nadeem U. Haque, examines recent IMF-developed empirical macroeconomic models dealing with adjustment and stabilization policies in developing countries. Some models are relevant for specific countries, and others relate to groups of developing countries.